Variable‐Temperature Electron Transport and Dipole Polarization Turning Flexible Multifunctional Microsensor beyond Electrical and Optical Energy. Issue 10 (29th January 2020) - Cao, Mao‐Sheng; Wang, Xi‐Xi; Zhang, Min; Cao, Wen‐Qiang; Fang, Xiao‐Yong; Yuan, Jie
Abstract: Humans are undergoing a fateful transformation focusing on artificial intelligence, quantum information technology, virtual reality, etc., which is inseparable from intelligent nano–micro devices. However, the booming of "Big Data" brings about an even greater challenge by growing electromagnetic radiation. Herein, an innovative flexible multifunctional microsensor is proposed, opening up a new horizon for intelligent devices. It integrates "non‐crosstalk" multiple perception and green electromagnetic interference shielding only in one pixel, with satisfactory sensitivity and fast information feedback. Importantly, beneficial by deep insight into the variable‐temperature electromagnetic response, the microsensor tactfully transforms the urgent threat of electromagnetic radiation into "wealth, " further integrating self‐power. This result will refresh researchers' realization of next‐generation devices, ushering in a new direction for aerospace engineering, remote sensing, communications, medical treatment, biomimetic robot, prosthetics, etc. Abstract : An innovative flexible multifunctional microsensor is demonstrated for the first time, holding highly integrated functions of "non‐crosstalk" multiple perception, green electromagnetic interference shielding, and self‐power only in one pixel. Importantly, insight into the variable‐temperature electromagnetic response is obtained, showing a new concept toward next‐generation intelligent devices in the coming era of the "Internet of Everything".